Allium cepa Bio Assay to Assess the Water and Sediment Cytogenotoxicity in a Tropical Stream Subjected to Multiple Point and Nonpoint Source Pollutants - W. M. Dimuthu Nilmini Wijeyaratne; L. G. Y. J. G. Wadasinghe (Journal of Toxicology)
The present study was conducted to assess the cytotoxicity of water and sediments of an industrial effluent receiving water body in the western province of Sri Lanka using Allium cepa bioassay. Six sampling sites (Site A: Urban; B: Industrial; C: Water intake for public water supply; D: Industrial; E: Agricultural; F: Reference) were selected from the study area. Ten replicate water and sediment samples were collected from each site, and physical and chemical parameters were measured using standard analytical methods. Cytotoxicity of water and sediment elutriates were measured using Allium cepa bioassay. Despite the significant spatial variations, the overall water and sediment quality parameters of the study sites were in accordance with the standard ambient environment parameters to sustain a healthy aquatic life. In the A. cepa bulbs exposed to water samples, significant root growth variations were not observed within 48 hours of exposure. However, significant root length variations were observed in A. cepa bulbs exposed to sediment elutriates within the 48-hour exposure and the percentage root growth inhibition increased with increase of exposure time. Similar trend was observed in mitotic activity indicating significantly lower mitotic indices (compared to that of the reference site) in A. cepa root tip cells exposed to sediment elutriates than those exposed to water samples. Further, the highest number of nuclear abnormalities was recorded from root tip cells of A. cepa exposed to water and sediment samples from sites B, C, and D. Therefore, it is of extreme importance to identify the composition and speciation of these cytogenotoxic compounds in the tropical climatic conditions and to propose possible clean-up or treatment solutions to overcome this environmental and public health risk associated problem.